Narrative Time And Moral Encoding In English And Uzbek Legends - O’sarova, Nilufar Yakubovna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article examines the structural and semantic peculiarities of narrative time and moral encoding in English and Uzbek legends from a comparative lingua-cultural perspective. Legends, as a form of traditional narrative, play a crucial role in preserving cultural memory and transmitting ethical values across generations. The study focuses on how temporal organization and moral meaning are linguistically and culturally constructed in the two traditions. The analysis reveals that English legends typically employ a linear and chronological model of narrative time, where moral meanings are conveyed implicitly through character behavior and narrative outcomes. In contrast, Uzbek legends demonstrate a more flexible and sometimes cyclic perception of time, accompanied by explicit and didactic moral expressions reinforced through proverbs and culturally significant symbols.